1997
DOI: 10.1029/96rs03691
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation rates, eddy diffusivity, and the Prandtl number: An in situ experimental approach and its consequences on radar estimate of turbulent parameters

Abstract: Abstract. Different methods have been proposed to derive the energy dissipation rate and eddy diffusion coefficients from ST radar measurements. However, their validity is still questionable because they implicitly assume that the Prandtl number is always equal to one, an assumption which is not verified. An experimental approach to this question, using balloon-borne experiment results, is proposed in this paper in order to test the validity/invalidity of the methods generally used. In situ observations show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 38 publications
6
55
2
Order By: Relevance
“…Ottersten, 1969;Weinstock, 1981;Bertin et al, 1997). It is based on the consideration of turbulence energy balance (see Ottersten, 1969) with the hypothesis of incompressibility, isotropic and stationary turbulence.…”
Section: Remarks About the Proposed Methodsmentioning
confidence: 99%
“…Ottersten, 1969;Weinstock, 1981;Bertin et al, 1997). It is based on the consideration of turbulence energy balance (see Ottersten, 1969) with the hypothesis of incompressibility, isotropic and stationary turbulence.…”
Section: Remarks About the Proposed Methodsmentioning
confidence: 99%
“…Barat and Bertin, 1984;Bertin et al, 1997;Hocking, 1999). The empirical constant α is taken as 0.5 (Bertin et al, 1997;Antonia et al, 1981). The Heisenberg model "breaks" at k 0 , which is the intersection of the asymptotic form of W (ω) in the inertial and viscous subrange.…”
Section: Appendix C Derivation Of the Inner Scale From The Heisenbergmentioning
confidence: 99%
“…In fact, several recent data have shown that mixing persists even after Ri = 1. These data include meteorological observations (Kondo et al 1978;Bertin et al 1997;Mahrt & Vickers 2005;Uttal et al 2002;Poulos et al 2002;Banta et al 2002), lab experiments (Strang & Fernando 2001;Rehmann & Koseff 2004;Ohya 2001), LES Zilitinkevich & Esau 2007), DNS (Stretch et al 2001), oceanic measurements (Mack & Schoeberlein 2004), and theoretical modeling (Sukoriansky et al 2005). constructed a model called "energy and flux-budget turbulence closure" that has no Ri(cr).…”
Section: Features Of the Model: No Ri(cr)mentioning
confidence: 99%